Immobilization by 21 days of bed rest results in type II collagen degradation in healthy individuals - Liphardt, Anna-Maria; Godonou, Elie-Tino; Dreiner, Maren; Mündermann, Annegret; Tascilar, Koray; Djalal, Nadja; Heer, Martina; Schett, Georg; Zaucke, Frank; Niehoff, Anja (Osteoarthritis and Cartilage, 2023)
Objective: To investigate the effects of 21 days of bed rest immobilization (with and without exercise and nutrition interventions) on type II collagen biomarker concentrations in healthy individuals. Design: Twelve healthy male participants (age 34.2 ± 8.3 years; body mass index 22.4 ± 1.7 kg/m²) were exposed to 6 days ambulatory baseline data collection (BDC), 21 days head-down-tilt bed rest (HDT, CON) + interventions (HDT + resistive vibration exercise (2 times/week, 25 minutes): RVE; HDT + RVE + whey protein (0.6 g/kg body weight/day) and bicarbonate supplementation (90 mmol KHCO3/day: NeX), and 6 days of re-ambulation (R) in a cross-over designed study. The starting HDT condition was randomized (CON-RVE-NEX, RVE-NEX-CON, NEX-CON-RVE). Blood and urine samples were collected before, during, and after HDT. Serum concentrations (s) of CPII, C2C, C1,2C, and urinary concentrations (u) of CTX-II and Coll2–1NO2 were measured. Results: Twenty-one days of HDT resulted in increased sCPII (p < 0.001), sC2C (p < 0.001), and sC1,2C (p = 0.001) (highest increases: sCPII (+24.2% - HDT5), sC2C (+24.4% - HDT7), sC1,2C (+13.5% - HDT2). sC2C remained elevated at R+1 (p = 0.002) and R+6 (p < 0.001) compared to baseline. NeX led to lower sCPII (p < 0.001) and sC1,2C (p = 0.003) compared to CON. uCTX-II (second void and 24-hour urine) increased during HDT (p < 0.001, highest increase on HDT21: second void +82.8% (p < 0.001); 24-hour urine + 77.8% (p < 0.001). NeX resulted in lower uCTX-II concentrations in 24-hour urine (p = 0.012) compared to CON. Conclusions: Twenty-one days of bed rest immobilization results in type II collagen degradation that does not recover within 6 days of resuming ambulation. The combination of resistive vibration exercise and protein/bicarbonate supplementation minimally counteracted this effect.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Bed rest; Cartilage biomarkers; Collagen metabolism; Immobilization; MNX-study; Type II collagen